Estimación de la técnica in vitro de gases frente a otras técnicas de digestibilidad - Vargas Bayona, Javier; Mejía Porras, Germán; Bedoya Mashuth, Julia; Gómez Patiño, Juan Felipe (Spei Domus, 2013)
To estimate the metabolism of the food consumed by ruminants, various nutritional analysis techniques have been developed to provide valuable information for research into animal nutrition. Objectives include criteria to increase productive efficiency in tropical production systems, particularly when tropical forages are the nutritional basis for ruminants. Thus, the motivation to review and document different digestibility techniques to determine the best choice among national and international references. The aim was to review the literature about for age digestibility techniques developed for estimating the overall behavior of foods in ruminants. More than 50 references were reviewed, obtaining information on in vivo, in situ and in vitro digestibility techniques along with their limitations and advantages. It can thus be inferred that these techniques have become very important biotrial tools, given that they are easy to carry out, reduce costs and can be applied locally. They provide valuable information, particularly in view of the small number of studies on tropical forages. Based on the forage digestibility techniques findings, we may conclude that the in vitro gas production digestibility technique is the most versatile tool, with accessible and instructive procedures and at lower cost; it is also more compatible with animal welfare regulations because it uses feces as inoculums. However, further studies need to be carried out regarding the inoculums used, given the need for protocol standardization and because kinetic behavior in the trials has not produced the expected results.